3G technology controlled brushless DC motor drive system using hybrid bacterial foraging–particle swarm optimisation. (13th February 2015) - Bayoumi, Ehab H.E.; Salmeen, Zaid A.
Instant messaging among mobile phone allows rapid transmission of short messages that permit any person to share ideas, opinions and other appropriate information. In this paper, the proposed control system is based on the 3G technology, which allows sending a text message with the control command from a remote area to the desired location. The mathematical model and the design PID speed controller for the brushless DC motor drive system are presented. A Hybrid Bacterial Foraging Particle Swarm Optimisation (HBF–PSO) algorithm is employed in order to obtain the controller parameters assuring enhanced step response performance criterion. Simulation results of the designed controllers are compared with that of classical evolutionary algorithm controllers whose parameters are adjusted using Practical Swarm Optimisation (PSO) and Bacterial Foraging Optimisation (BFO). Experimental and simulations results signify the superiority of the proposed technique over the PSO and BFO methods and allow the proposed system a greater degree of freedom to control and monitor the electric drive system.